The Influence of Latitude on the Climatic Characteristics of Classroom in Campus 1 and Campus 2 of Khairun University in Achieving Adaptive Thermal Comfort - Tayeb Mustamin; Nasrullah; Sayyid Quraisy; Aswar Masri (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Microclimate variables are important factors that affect adaptive thermal comfort. These factors include air temperature, solar radiation, air humidity, and wind speed. This study focuses on discussing microclimate variables, specifically air temperature and air humidity. This is based on previous research indicating that the most influential climate variables are air temperature, solar radiation, and air humidity. This study is a field research aimed at comparing air temperature and air humidity between campus 1 and campus 2 of Khairun University, due to differences in geographical elevation. Measurements were taken in March. The variables of air temperature and air humidity were measured inside the building. The research results show significant differences between campus 1 and campus 2. These differences can be associated with the perceived adaptive thermal comfort by the users. The thermal sensation results direct that the majority of users in campus 2 feel cool, while the majority of users in campus 1 feel comfortable or neutral. These findings provide a strong basis for improving adaptive thermal comfort in both campuses by considering optimal air temperature and air humidity settings.